Determination the groundwater effects on corrosion in Nano composite material Silicon- Carbide reinforced aluminum alloys in Baghdad Iraq. - Mamoon A A Al-Jaafari; Israa Fadhil Ibraheem (Zien Journals, 2022)
This article presents the results of a study to determine the effects of groundwater on the mechanical properties of an aluminum alloy. The corrosion was evaluated on this aluminum alloy that was subjected to an aqueous solution attack from a four-point extractor at a depth of (4-4.5) meter in an area west of Baghdad. The results indicated that the addition of silicon carbide nanoparticles improved the properties. The mechanical strength of the base alloy, especially at a ratio 2.0 wt.%, significantly reduced the rate of pitting
Keywords: Nanotechnology; Nano composite; Aluminum nano composite; Corrosion of material